KAWASAKI DISEASE EXPERIENCE AT TERTIARY CARE HOSPITAL RAWALPINDI, PAKISTAN: Kawasaki Disease Experience - Mahmud, Shahid; Shah, Syed Awais Ul Hassan; ., Shahneela (Pakistan Armed Forces Medical Journal, 2018)
Objective: To study the clinical features, investigations, cardiac complications, effects of treatment and demographic profiles in patients with classical Kawasaki disease (KD). Study Design: Descriptive study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Jan 2007 to Dec 2011. Patients and Methods: Twenty five children of either gender aged 2 months to 12 years diagnosed with KD based on the international diagnostic criteria were included in this study. Collected data included patient demographics, clinical features, investigations, echo-cardio graphic findings, treatment and follow-up. Results: A total of 25 patients were evaluated during the above mentioned duration. Mean age at diagnosis was 3.7 years (SD ± 3.05). Fever was present in 100% of the patients with the other major diagnostic features present in more than 90% of the patients. Seventeen (68%) patients presented after ten days of fever. Coronary aneurysms were seen in 40% of the patients. We administered intravenous immune-globulins (IVIG) in 100% of the patients. 12% of the patients still had coronary aneurysms after 1 year of diagnosis. There was no mortality. Conclusion: KD needs to be considered in the differential diagnosis of all children with persistent unexplained fever with rash. A great number of cases of KD are missed and treated as common cold or flu. Diagnostic criteria used for KD is helpful in diagnosis of KD and can help in early prompt treatment with IVIG to prevent the life threatening complication of coronary aneurysms.